2012
DOI: 10.2987/11-6139.1
|View full text |Cite
|
Sign up to set email alerts
|

Pyriproxyfen for the Control of Australian Salt-Marsh Mosquito, Aedes vigilax

Abstract: The efficacy of pyriproxyfen against the Australian salt-marsh mosquito, Aedes vigilax, was examined in 2 laboratory and 1 semi-field study using both technical grade and formulated products. In a dose-response study, the median emergence inhibition (EI50) and EI95 values were determined to be 0.019 and 0.076 ppb, respectively, for pyriproxyfen technical grade, 0.021 and 0.092 ppb for a microencapsulated formulation (Sumilarv 90CS), and 0.054 and 0.236 ppb for the formulated s-methoprene product, Altosid Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…albopictus. Pyriproxyfen works effectively at very low doses (Invest and Lucas 2008, Devine et al 2009, Webb et al 2012). In the Þeld, Sihuincha et al (2005) obtained Ͼ90% control of Ae.…”
mentioning
confidence: 97%
“…albopictus. Pyriproxyfen works effectively at very low doses (Invest and Lucas 2008, Devine et al 2009, Webb et al 2012). In the Þeld, Sihuincha et al (2005) obtained Ͼ90% control of Ae.…”
mentioning
confidence: 97%
“…23) JHA pyriproxyfen inhibits adult emergence of Australian salt-marsh mosquito, Aedes vigilax. 24) Pyriproxyfen was shown to inhibit Aedes japonicus adult emergence after exposure of 3rd or 4th instar larvae to this insecticide. Addition- ally, gravid adult females were used to auto-disseminate pyriproxyfen powder to larval development habitats to inhibit adult emergence.…”
Section: Jha Application Kills Pupae But Not Larvae In Some Insectsmentioning
confidence: 97%
“…Methoprene is the most widely used JHA for controlling mosquito larvae. 22,23,[29][30][31][35][36][37][38][39][40][41][42][43][44][45] However, recent studies showed the efficacy of pyriproxyfen for larval control and adult sterilization of various mosquito species, 24,28,[32][33][34] which might increase the use of this chemical for vector control. In contrast, hydroprene was not used much for mosquito control.…”
Section: Jha Efficacy Is Variable Among Insect Pests and Disease Vectors Testedmentioning
confidence: 99%
“…tritaeniorhynchus Giles for .3 wk in open containers and irrigation ditches at 0.01 ppm, cesspools at 0.05 ppm, and in sewers with wastewater at 0.1 ppm in Japan (Kamumura and Arakawa 1991); it has also been reported to cause complete IAE of Aedes togoi (Theobald) in brackish water at 0.05 ppm in Korea (Lee 2001). In a semifield study, Webb et al (2012) reported a complete control of the Australian salt-marsh mosquito, Ae. vigilax (Skuse), by a granular formulation of pyriproxyfen (Sumilarv 0.5G) for 2 wk posttreatment with a high (28%) IAE in control, which they attributed to abnormally cool weather during the test.…”
Section: Introductionmentioning
confidence: 99%